Attention Deficit Hyperactivity Disorder and Treatment Adherence in Adolescent Acne Patients: Investigating the Relationship for Better Care Strategies - Huriye Aybüke Koç; Cansu Altınöz Güney; Bedia Sultan Önal (Dermatology Practical & Conceptual)
Introduction: Accompanying comorbidities in acne vulgaris (AV) patients affect treatment adherence.